Construction of a fully conjugated cross-linked hole-transport film based on ethynyl to enable high mobility for efficient solution-processed OLEDs. Issue 39 (15th September 2022) - Peng, Cancan; Liu, Hongli; Han, Xinjun; Zhang, Fei; Wang, Shirong; Li, Xianggao
Abstract : Ethynyl-based cross-linkable hole transport material E-TPD was designed to obtain fully conjugated cross-linked hole transport film with preferable hole mobility. The solution-processed OLED gained excellent performance with CEmax of 60.74 cd A −1 . Abstract : The utilization of cross-linked hole transport layers is deemed as an effective strategy to solve the interlayer miscibility problem in solution-processed organic light-emitting diodes (OLEDs). However, the general incomplete conjugated structure after cross-linking makes it incapable for high hole mobility. In this study, a novel hole transport material N, N ′-bis(4-ethynylphenyl)-[1, 1′-biphenyl]-4, 4′-diamine (E-TPD) with cross-linkable ethynyl groups was designed and synthesized to construct a fully conjugated cross-linked hole transport film. The thermal properties, cross-linking characteristics, photophysical properties, surface morphology, and hole transport ability were studied in detail. The cross-linked E-TPD (p(E-TPD)) film demonstrated a suitable highest occupied molecular orbital (HOMO) energy level, excellent solvent resistance and uniform film morphology. Particularly, its hole mobility reached a high value of up to 8.2 × 10 −4 cm 2 V −1 s −1, which is over three times than that of N, N ′-di- p -tolyl- N, N ′-bis(4-vinylphenyl)-[1, 1′-biphenyl]-4, 4′-diamine (V-p-TPD) (2.5 × 10 −4 cm 2 V −1 s −1 ) with the same core structure based on cross-linkable vinyl groups. The corresponding solution-processed green phosphorescent OLED gained excellent performance with a turn-on voltage ( V on ) of 3.3 V, maximum current efficiency (CEmax ) of 60.74 cd A −1 and maximum external quantum efficiency (EQEmax ) of 17.33%. This study provides a novel tactic to achieve a high-mobility cross-linked hole transport layer by constructing a fully conjugated structure for solution-processed OLEDs.